Challenges and Assets of Older Adults in Sub-Saharan Africa: Perspectives of Gerontology Scholars. Issue 1 (2nd January 2022) - Adamek, Margaret E.; Gebremariam Kotecho, Messay; Chane, Samson; Gebeyaw, Getachew
ABSTRACT: Life expectancy is increasing globally, with the biggest gains expected in sub-Saharan Africa. Using an online survey, we investigated the perspectives of gerontology scholars on the challenges of aging in sub-Saharan Africa as well as the assets of older adults. Respondents (n = 72) from 17 countries, primarily in Africa, and representing 16 disciplines, identified the top issues facing African older adults as: poverty, lack of trained geriatric professionals, food insecurity, disability/health issues, and long-term care. Older adults' unique strengths were noted as indigenous knowledge systems, being holders of cultural heritage, and their contributions to development. Respondents' biggest concerns about older adults in sub-Saharan Africa were the lack of government attention to aging issues (63%) and a lack of social services targeted to older adults' needs (57%). Government funding (77.8%) and international partnerships (38.9%) were noted as resources needed to support aging research in sub-Saharan Africa. The response or non-response of governments in sub-Saharan Africa will determine whether the growing number of older adults will increasingly experience unmet needs and whether their assets will be considered in development efforts. Establishing professional networks of gerontology scholars in the region will help to document the challenges faced by older adults, to plan for the coming demographic shift, and to empower older adults to thrive as valued community members.